2019
DOI: 10.1002/ajpa.23879
|View full text |Cite
|
Sign up to set email alerts
|

Place of origin of the sacrificial victims in the sacred Cenote, Chichén Itzá, Mexico

Abstract: Objectives: The ancient city of Chichén Itzá in the northern Yucatán of Mexico was one of the most important in the Maya area, but its origins and history are poorly understood. A major question concerns the origins of the peoples who founded and later expanded the ancient city. Hundreds of people were ritually executed and their bodies thrown into the waters of the Sacred Cenote at Chichén. Materials and methods: In this study, we use strontium and oxygen isotopes to study the place of origin of a large sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 69 publications
1
10
0
1
Order By: Relevance
“…For example, small numbers of samples with narrow ranges may include outlier values that would be considered “local” in a larger dataset in an area with greater geologic diversity and/or catchment use. In addition, strontium isotope values in the Maya region are similar to those identified elsewhere in Meso- and Central America and the Caribbean (Laffoon et al 2012; Miller Wolf and Freiwald 2018; Price et al 2008, 2019). Isotope values are simply numbers, and additional lines of evidence, from texts to burial goods, are critical for the interpretation of their meaning.…”
Section: Isotopic Migration Methodssupporting
confidence: 79%
See 2 more Smart Citations
“…For example, small numbers of samples with narrow ranges may include outlier values that would be considered “local” in a larger dataset in an area with greater geologic diversity and/or catchment use. In addition, strontium isotope values in the Maya region are similar to those identified elsewhere in Meso- and Central America and the Caribbean (Laffoon et al 2012; Miller Wolf and Freiwald 2018; Price et al 2008, 2019). Isotope values are simply numbers, and additional lines of evidence, from texts to burial goods, are critical for the interpretation of their meaning.…”
Section: Isotopic Migration Methodssupporting
confidence: 79%
“…
Figure 2.Strontium isotope values associated with Postclassic and Colonial centers in and around the Maya region. For detail, see Freiwald (2020a), Freiwald et al (2019), Miller Wolf and Freiwald (2018), Ortega-Muñoz et al (2019), Price et al (2006, 2008, 2019), and Suzuki et al (2015).
…”
Section: Isotopic Migration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The taxonomical composition of the assemblages suggests a high diversity of animal utilization, especially in domestic contexts most likely consumed as food resources. However, a different pattern of the role of animal protein in the human diet is suggested by isotopic evidence, as individuals from Yaxuna (Mansell et al 2006) and victims from the Sacred Cenote in CI (Price et al 2019) indicated a diet mostly based on maize consumption and less animal protein consumption.…”
Section: Mammalsmentioning
confidence: 99%
“…1,2). The site was a politically powerful settlement and ceremonial center that participated in highland exchange 2020), Hodell et al (2004), and Price et al (2008Price et al ( , 2019. Note the Metamorphic Province contains the Motagua Valley, with a 87 Sr/ 86 Sr range of 0.07042-0.7073.…”
Section: Introductionmentioning
confidence: 99%